A Framework for the Eltonian Niche of Humans. (26th May 2021) - Moll, Remington J; Killion, Alexander K; Hayward, Matt W; Montgomery, Robert A
Abstract: Recent research has highlighted several influential roles that humans play in ecosystems, including that of a superpredator, hyperkeystone species, and niche constructor. This work has begun to describe the Eltonian niche of humans, which encompasses humanity's cumulative ecological and evolutionary roles in trophic systems. However, we lack a unifying framework that brings together these strands of research, links them to ecoevolutionary and sociocultural theory, and identifies current research needs. In this article, we present such a framework in hope of facilitating a more holistic approach to operationalizing human roles in trophic systems across an increasingly anthropogenic biosphere. The framework underscores how humans play numerous nuanced roles in trophic systems, from top-down to bottom-up, that entail not only pernicious effects but also benefits for many nonhuman species. Such a nuanced view of the Eltonian niche of humans is important for understanding complex social–ecological system functioning and enacting effective policies and conservation measures.